Uji Efektivitas Antimikroba Ekstrak Etanol 70% Buah Strawberry (Fragaria X Ananassa)Terhadap Pertumbuhan Bakteri staphylococcus aureus. Dan shigella sp. Secara In vitro - Purnama, Prala Ayu Aristya, Riandini Aisyah, S.Si.,M.Sc (2017)
Background :Strawberry (Fragaria x ananassa)is plant that has a potential effect as medical plant. Strawberry contains flavonoid, alkaloid, and saponin compound that have as an antibacterial effect. Objective :This research is aimed to determine the activity of ethanol extract of strawberry in inhibiting the growth of Staphylococcus aureus and Shigella sp. Methods : This research wasan experimental laboratory method with post test only control group design. The ethanol extract of strawberry (Fragaria x ananassa) was tested by well method with concentration 10%, 20%, 40%, 80% and 100 %. Well was made on mueller hilton germ growth media which smeared by culture of Staphylococcus aureus and Shigella sp which has been standardized by o,5 McFarland standard. The ethanol extract of strawberry (Fragaria x ananassa) drip into the well with various concentrations. Then it was incubated with a temperature of 37oC for 24 hours and the form inhibition zone was measured. The data was analyzed with kruskal-wallis non parametric test and post hoc Mann-Whitney test. Results :The ethanol extract of strawberry (Fragaria x ananassa) with concentration 10%, 20%, 40%, 80% and 100% can inhibit the growth of Staphylococcus aureus with means inhibition zona are10.24mm, 13.26mm, 16.37mm, 18.17mm, and 18.34mmand the value of statistic test p=0,000, while Shigella sp. with means of eachare15.33mm, 18.57mm, 20.85mm. 22.91mm, and 21.93mm with the value of statistic test p=0,000. Conclusion: The ethanol extract of strawberry (Fragaria x ananassa) has anti bacterial activity against Staphylococcus aureus and Shigella sp. in vitro.